New insights of cultural cannibalism amongst Magdalenian groups at Maszycka Cave, Poland - Francesc Marginedas; Palmira Saladié; Marta Połtowicz-Bobak; Thomas Terberger; Dariusz Bobak; Antonio Rodríguez-Hidalgo (Scientific Reports)
Abstract The manipulation of human corpses started to become commonplace during the Upper Paleolithic. This well-documented behavior among Magdalenian peoples consists of perimortem manipulation and the removal of soft tissues and has been understood as forming part of the cultural repertoire of mortuary actions. The study of these practices has given rise to several interpretations with the consumption of human flesh (cannibalism) occupying a central position. The human assemblage of Maszycka Cave (18,000 cal. BP) is part of this ongoing debate. Although initial research in the 1990s suggested cannibalism, more recent studies challenge this interpretation arguing that the low incidence of human activity rule out the likelihood of processing for the purpose of consumption and proposing skull selection as a funerary practice. This study reviews the assemblage and presents previously unpublished postcranial skeletal specimens along with evidence of whole-body manipulation for consumption. This behavior is also observed in other chronologically and culturally similar assemblages throughout continental Europe, suggesting that cannibalism was integral practice within the cultural systems of these Magdalenian groups.